Budget Impact Analysis of Minimally Invasive versus Open Transforaminal Lumbar Interbody Fusion for Lumbar Degenerative Disease: A European Hospital Perspective - Bassani R; Galvain T; Battaglia S; Maheswaran H; Wright G; Kambli A; Piemontese A (Dove Medical Press, 2024)
Roberto Bassani,1 Thibaut Galvain,2 Suzanne Battaglia,3 Hendramoorthy Maheswaran,4 George Wright,5 Ankita Kambli,5 Alessandra Piemontese3 1II Spinal Surgery Unit, IRCCS Galeazzi-Sant'Ambrogio Hospital, Milano, Italy; 2Johnson and Johnson MedTech, Issy-les-Moulineaux, France; 3Johnson and Johnson MedTech, Pomezia, Italy; 4Johnson and Johnson MedTech, London, UK; 5EVERSANA, Burlington, Ontario, CanadaCorrespondence: George Wright, EVERSANA, 113-3228 South Service Road, Burlington, Ontario, L7N 3H8, Canada, Tel +1 513-827-3035, Email george.wright@eversana.comPurpose: When traditional therapies fail to provide relief from debilitating lower back pain, surgeries such as transforaminal lumbar interbody fusion (TLIF) may be required. This budget impact analysis (BIA) compared minimally-invasive (MI)-TLIF versus open (O)-TLIF for single-level fusion from an Italian hospital perspective.Methods: The BIA compared costs of 100 MI-TLIF and 100 O-TLIF procedures from an Italian hospital perspective over a one-year time horizon. The base case included costs for length of hospital stay (LOS), blood loss, and sterilizing surgical trays. The scenario analysis also included operating room (OR) time and complication costs. Base case inputs were from the Miller et al meta-analysis; scenario analysis inputs were from the Hammad et al meta-analysis. The device costs for MI-TLIF and O-TLIF procedures were from Italian tender prices for Viper Prime™ System and Expedium™ Spine System, respectively.Results: Base case deterministic analysis results showed cost savings of € 207,370 for MI-TLIF compared with O-TLIF. MI-TLIF costs were lower for LOS (€ 215,277), transfusion for blood loss (€ 16,881), and surgical tray sterilization (€ 28,232), whereas device costs were lower for O-TLIF (€ 53,020). The probabilistic result was similar, with MI-TLIF resulting in savings of € 211,026 (95% credible interval [CR]: € 208,725 - € 213,327). All 1000 base case probabilistic sensitivity analysis runs were cost saving. Deterministic scenario analysis results showed cost savings of € 166,719 for MI-TLIF. MI-TLIF costs were lower for LOS (€ 190,813), transfusion for blood loss (€ 16,881), surgical tray sterilization (€ 28,232), and complications (€ 2076), whereas O-TLIF costs were lower for OR time (€ 18,263) and devices used (€ 53,020).Conclusion: Despite the increase incremental cost for medical device innovation and OR time, this study demonstrates the economic savings of MI-TLIF compared to O-TLIF from a European hospital perspective. The findings will be useful to policy and hospital decision makers in assessing purchasing, funding and reimbursement decisions.Keywords: spine surgery, incremental cost, budget impact analysis, Italy, medical device innovation, health economic model